Preliminary Study on Kinetic Energy Distributions of Ar+ Fragments Resulting From Ar3+ Visible Photodissociation. Issue 2 (1991) - Gadea, F. X.; Durup, J.
Abstract : According to a strategy which involves DIM excitonic Hamiltonian, DIM-like transition dipole moments, realistic dynamical propagations with the HWD method (Hemiquantal dynamics with the Whole DIM basis), and the Wigner function to weight the initial conditions, a non-empirical theoretical study of the kinetic energy distribution of theAr + photofragments is performed for three total energies. The results illustrate the dominant symmetric stretching motion and the importance of non-adiabatic effects in theAr 3 + dissociation dynamics.